Relevance of Fatty Acids to Sperm Maturation and Quality. (5th February 2020) - Collodel, Giulia; Castellini, Cesare; Lee, Jetty Chung-Yung; Signorini, Cinzia
Abstract : Almost 50% of infertility cases are associated with human male infertility. The sperm membrane is a key structure influencing sperm morphology and function in normal and pathological conditions. The fatty acid profile determines the performance not only of sperm motility but also of acrosomal reaction and sperm-oocyte fusion. This review presents available knowledge on the role of fatty acid composition in human sperm and spermatogenesis and discusses the influence of dietary fatty acids on the sperm fatty acid profile. Recent studies in biological sciences and clinical researches in this field are also reported. The topic object of this review has potential application in medicine by identifying potential causes of infertility.